2021
DOI: 10.1021/acsnano.0c10208
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Graphene Base Hot-Electron Transistor

Abstract: The integration of graphene and other two-dimensional (2D) materials with existing silicon semiconductor technology is highly desirable. This is due to the diverse advantages and potential applications brought about by the consequent miniaturization of the resulting electronic devices. Nevertheless, such devices that can operate at very high frequencies for high-speed applications are eminently preferred. In this work, we demonstrate a vertical graphene base hot-electron transistor that performs in the radio f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…37 ) to facilitate the collection of hot electrons injected from the emitter. 15 And the electrode isolation of the base (B) and collector was achieved by depositing a 30 nm layer of Al 2 O 3 on Si substrate. A micron-wire N-type GaN (3 × 10 18 )/AlN transferred on graphene by an organic solvent droplet method is an emitter (E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 ) to facilitate the collection of hot electrons injected from the emitter. 15 And the electrode isolation of the base (B) and collector was achieved by depositing a 30 nm layer of Al 2 O 3 on Si substrate. A micron-wire N-type GaN (3 × 10 18 )/AlN transferred on graphene by an organic solvent droplet method is an emitter (E).…”
Section: Resultsmentioning
confidence: 99%
“…Further, Lan et al also experimentally demonstrated that Si/SiO 2 /Gr/ MoS 2 /h-BN can work at frequencies of up to 65 GHz, which is one of the best-performing GHET devices developed to date. 15 Although the barrier difference between Gr and h-BN (2.56 eV) is smaller than that of Al 2 O 3 (3.3 eV), it still results in a large amount of hot electron reflection, and the common emitter current gain is only 2. the current gain, Zeng et al inserted the insulating layer of alumina between the base and the collector as a shield layer to filter the cold electrons, achieving 40% of the common base current gain. 16 Recently, Xu et al verified that configurations with high-barrier (Gr/h-BN/Gr) injected hot electrons and low-barrier (Gr/WSe 2 /Gr) filtered cold electrons achieved the highest collection efficiency at the minimum collection voltage, approaching the theoretical limit of 99.9%.…”
Section: Introductionmentioning
confidence: 99%
“…22 Quantum tunneling transistors based on 2D materials consist of van der Waals heterostructures that can utilize a pure quantum tunneling mechanism and theoretically allow THz frequencies, not only at low temperature but also at room temperature, due to the ballistic transport of the carriers, thus resulting in faster transit times and high-speed operation. [23][24][25][26] In our previous work, we have proposed graphene-base hot electron transistors (GHETs), which are an example of the well-known vertical graphenebased class of quantum tunneling transistors, [27][28][29][30][31][32][33] that allow measurements of device performance over a frequency range in the tens of GHz. 33 In this research, for the first time, we present a GHET formed from the layer-by-layer stacking of 2D materials (graphene, MoS 2 , and h-BN) that can operate as a frequency modulator.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] In our previous work, we have proposed graphene-base hot electron transistors (GHETs), which are an example of the well-known vertical graphenebased class of quantum tunneling transistors, [27][28][29][30][31][32][33] that allow measurements of device performance over a frequency range in the tens of GHz. 33 In this research, for the first time, we present a GHET formed from the layer-by-layer stacking of 2D materials (graphene, MoS 2 , and h-BN) that can operate as a frequency modulator. In our GHET architecture, a native SiO 2 layer is selected as a tunneling barrier between the Si emitter and the graphene base region instead of a traditional chemical vapor deposition-grown (CVD-grown) oxide material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation